2008
DOI: 10.1021/jf073041o
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Analysis of Tronchuda Cabbage (Brassica oleracea L. var. costata DC) Phenolics: Influence of Fertilizers

Abstract: A field experiment was carried out to investigate the effect of fertilization level on the phenolic composition of tronchuda cabbage (Brassica oleracea L. var. costata DC) external and internal leaves. Eight different plots were constituted: a control without fertilization, one with organic matter, and six experiments with conventional fertilizers (nitrogen, boron, and sulfur, two levels each). The phenolic compounds were analyzed by reversed-phase HPLC-DAD. External and internal leaves revealed distinct quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 35 publications
5
41
0
3
Order By: Relevance
“…Pearson correlation indicated a strong negative relationship between plant height and TFC and TPC which is in line with the findings of (Ogembo 2015, Sousa et al 2008) who demonstrated higher levels of total phenolics were accompanied by lower plant growth in Solanum and Brassica species. Phenolics and flavanoids (quarcetin) concentrations increase was observed under inhibited plant growth in Amaranthus hypochondriacus (Onyango et al 2012).…”
Section: Relationship Between Plant Growth and Tfc And Tpc Concentrationsupporting
confidence: 77%
“…Pearson correlation indicated a strong negative relationship between plant height and TFC and TPC which is in line with the findings of (Ogembo 2015, Sousa et al 2008) who demonstrated higher levels of total phenolics were accompanied by lower plant growth in Solanum and Brassica species. Phenolics and flavanoids (quarcetin) concentrations increase was observed under inhibited plant growth in Amaranthus hypochondriacus (Onyango et al 2012).…”
Section: Relationship Between Plant Growth and Tfc And Tpc Concentrationsupporting
confidence: 77%
“…sabellica), broccoli and brussels sprouts (Milder et al, 2005). The glycosylated flavonoids and simple phenolics such as 3-sophoroside-7-glucosides of kaempferol, quercetin and isorhamnetin and hydroxyl-cinnamates reported in the Brassicaceae (Durkeet and Harborne, 1973;Francisco et al, 2009;Jahangir et al, 2009;Podsę dek, 2007;Sousa et al, 2008), are increasingly attributed beneficial health effects such as reduced risk of age-related chronic diseases, like cancers and cardiovascular disease, and advantageous manipulation of gut microbiota (Clifford, 2004;Graf et al, 2005;Lee and Lee, 2006;Terao et al, 2008;Williamson et al, 2000).…”
Section: Polyphenolics and Healthmentioning
confidence: 99%
“…As the carbon/nutrient balance theory predicts, in terms of a high plant photosynthetic activity relative to the nitrogen supply, the excess of carbon is allocated to phenolics, a nitrogen-free defense substance (Yongke et al, 2005). Recent work by Sousa et al (2008) demonstrated an overall trend of higher total phenolics concentration in organically grown tronchuda cabbage, accompanied by lower plant fresh weight, as compared with conventionally fertilized samples. They suggested that the lack of nutrients, particularly insufficient nitrogen supply as a result of a low mineralization rate under organic production, could have boosted synthesis of phenolic compounds while limiting rapid growth of new leaves.…”
Section: Total Phenolic and Quercetin Contentsmentioning
confidence: 99%